2021
DOI: 10.54623/fdj.7024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Remaining Dentin Thickness After Manual and Evaluation of Remaining Dentin Thickness After Manual and Rotary Instrumentation In Primary Molars Using Cone Beam Rotary Instrumentation In Primary Molars Using Cone Beam Computed Tomography. (An In-Vitro Study)

Abstract: Aim: To compare the radicular dentin thickness before and after instrumentation by manual stainless-steel (K-files) versus rotary files (AF™ Baby File) at coronal, middle, and apical thirds using Cone Beam Computed Tomography (CBCT). Materials and Methods: Forty roots of extracted mandibular primary molars were collected, and randomly and equally divided into 2 groups. Manual Group was prepared by K-files, and Rotary Group was prepared by rotary AF™ Baby File system. Samples were decapitated and stabilized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Whereas a significant difference in the middle third was found between the same groups with less amount of dentin removed in the Fanta AF™ Baby group; this may be attributed to less flexible stainless-steel K-files that can force against the dentinal walls laterally and effectively remove more dentin [ 34 ], contrasted to controlled memory (CM) wires technology of Fanta AF™ Baby files that easily adapt to diverse canals morphology without straightening [ 10 ]. This agreed with Eldemery et al [ 30 ] who found that the K-file group had a higher amount of dentin removed than the Fanta AF™ Baby group at all levels of the root canal with a highly significant difference. Also, Kummer et al [ 13 ] revealed that K-file instrumentation removed more dentin than rotary instrumentation (Hero 642).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Whereas a significant difference in the middle third was found between the same groups with less amount of dentin removed in the Fanta AF™ Baby group; this may be attributed to less flexible stainless-steel K-files that can force against the dentinal walls laterally and effectively remove more dentin [ 34 ], contrasted to controlled memory (CM) wires technology of Fanta AF™ Baby files that easily adapt to diverse canals morphology without straightening [ 10 ]. This agreed with Eldemery et al [ 30 ] who found that the K-file group had a higher amount of dentin removed than the Fanta AF™ Baby group at all levels of the root canal with a highly significant difference. Also, Kummer et al [ 13 ] revealed that K-file instrumentation removed more dentin than rotary instrumentation (Hero 642).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the greatest amount of dentin removed was noticed in the Fanta AF™ Baby group at the cervical and apical thirds among the study groups; this may be attributed to the constant file taper (0.04 ISO) along the entire file length also, the total number of files used in the instrumentation procedures [ 30 ]. A non-significant difference was found between Fanta AF™ Baby and K-file groups at cervical and apical third with a great amount of dentin removed in both groups; this may be linked to the total file number of Fanta AF™ Baby (four files) and K-files (six files) used during the root canal preparation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These files conform to the root canal shape and don’t totally straighten through curved canal instrumentation. Fanta AF ™ Baby file has a triangular cross-section with16 mm working length that reduces the stress by minimizing contact between the file & dentin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%